Evaluation of Recovery Strategy and Digital Transformation on BNI's Financial Performance Post COVID-19 Pandemic - Aslam, Annisa Paramaswary; Yasir, Muhammad; Rahim, Fitriani (Nusantara Economics and Entrepreneurships Journals, 2025)
This study aims to evaluate the financial performance of PT Bank Negara Indonesia (Persero) Tbk. during the period from 2020 to 2024, considering the impact of the COVID-19 pandemic and the role of digital transformation in the recovery process. The analysis uses key financial ratios, including Return on Assets (ROA), Return on Equity (ROE), the Operating Expense to Operating Income ratio (BOPO), and Net Profit Margin (NPM). A descriptive quantitative method is employed, using documentary study from BNI's annual financial reports and secondary data from the Financial Services Authority (OJK). The analysis results show that 2020 was the most challenging year for BNI, with a sharp decline in profitability and efficiency indicators. However, from 2021 to 2024, there was significant recovery across almost all financial indicators, reflecting the success of cost-efficiency strategies, asset productivity improvements, and the implementation of digital services. This study underscores the importance of adapting banking strategies to face crises and foster long-term growth through digital transformation.